Peningkatan Berpikir Kritis Matematis Melalui Pendekatan Saintifik pada Materi Relasi dan Fungsi - Siregar, Rosmita Sari SIregar (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to compare the mathematical critical thinking abilities of students whoreceive a scientific approach with students who receive conventional learning. This study uses experimentalmethods. The subjects were MTSN 2 Medan students who were randomly selected from two classes in classVIII. These two classes were chosen randomly to be used as the experimental class and control class. Theexperimental class received learning with a scientific approach, while the control class received conventionallearning. The mathematical critical thinking ability test is the instrument used. The results of data analysis showthat scientific learning methods improve students' mathematical critical thinking abilities.